Prevalence and antimicrobial susceptibility profile of bacteria isolated from the hands of housemaids in Jimma City, Ethiopia - Ango, Tadele Shiwito; Gelaw, Negalgn Byadgie; Zegene, Girma Mamo; Teshome, Tizita; Getahun, Tesfalem (Frontiers in Public Health, 2024)
Bacterial pathogens continue to be major causes of foodborne gastroenteritis in humans and remain public health problems. Housemaids operating inside a kitchen could be the source of infection and may transmit disease-inflicting pathogens through contaminated hands.Objective: This study aimed to assess the prevalence and antimicrobial susceptibility profile of bacteria isolated from the hands of housemaids in Jimma City, Ethiopia.: Laboratory-based cross-sectional study was employed among 234 housemaids. Hand swab samples from the dominant hand of the study participants were collected under sterile conditions following standard operating procedures. Then in the laboratory, the swabs were inoculated aseptically using streak-plating methods on the growth media like on the mannitol salt agar [S. aureus and Coagulase-negative staphylococci], macconkey agar [Klebsiella species and Proteus species], salmonella-shigella agar [Salmonella species and Shigella species], and eosin methylene blue agar [E. coli]. In addition, a set of biochemical tests was applied to examine bacterial species. Data were double-entered into Epidata version 3.1 and then exported to the statistical package for social science statistics version 26 for further analysis. Descriptive analyses were summarized using frequency and percentage.The overall prevalence of one or more positive bacteria isolates from the hands of housemaids was 72% (95% CI: 66.2, 77.8). The dominant bacteria isolates were S. aureus (31.6%), E.coli (21.3%), Klebsiella species (23.1%), and Proteus species (14.7%). The majority of S. aureus was susceptible to chloramphenicol (98.6%). E. coli isolates were sensitive to tetracycline (75%), ceftriaxone (79.2%), chloramphenicol (87.5%), and ceftazidime (77.1%). In addition, Klebsiella (88.5%) and Proteus species (100%) were sensitive to chloramphenicol. However, about 28.2% of isolated S. aureus were resistant to tetracycline. Moreover, one-quarter of isolated E. coli were resistant to tetracycline, ceftriaxone, chloramphenicol, and ceftazidime. Shigella and Proteus species were resistant to tetracycline and ceftriaxone.Hands of housemaids are important potential sources of pathogenic bacteria that would result in the potential risk of foodborne diseases. Most bacteria isolates were resistant to tetracycline, ceftriaxone, and ceftazidime. Therefore, practicing good hand hygiene helps to prevent and control the spread of antimicrobial-resistant microbes.